Evaluation of a material parameter extraction algorithm using MRI-based displacement measurements - Romano, A.J.; Bucaro, J.A.; Ehnan, R.L.; Shirron, J.J. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2000)
The performance of an inversion algorithm is investigated when applied to measured displacement data for a determination of the material parameters /sup /spl lambda/+2/spl mu///sub /spl rho// (longitudinal wave velocity squared) and /sup /spl mu///sub /spl rho// (shear wave velocity squared) throughout an inhomogeneous test phantom. The vector displacement components throughout a test phantom subject to monochromatic shear excitation measured in time using magnetic resonance imaging (MRI) were temporally Fourier transformed to extract the component of monochromatic excitation, and the data was delivered to the inversion algorithm. A series of inversions is presented demonstrating the effects of subsequent wavenumber filtering, polarization selection, and variation in the size of the incremental volume elements. The resulting performance is assessed, and recommendations for future efforts are discussed.